Sensitization of dural afferents underlies migraine-related behavior following meningeal application of interleukin-6 (IL-6) - Yan, Jin (BioMed Central, 2012)
BACKGROUND: Migraine headache is one of the most common neurological disorders, but the pathophysiology contributing to migraine is poorly understood. Intracranial interleukin-6 (IL-6) levels have been shown to be elevated during migraine attacks, suggesting that this cytokine may facilitate pain signaling from the meninges and contribute to the development of headache. METHODS: Cutaneous allodynia was measured in rats following stimulation of the dura with IL-6 alone or in combination with the MEK inhibitor, U0126. The number of action potentials and latency to the first action potential peak in response to a ramp current stimulus as well as current threshold were measured in retrogradely-labeled dural afferents using patch-clamp electrophysiology. These recordings were performed in the presence of IL-6 alone or in combination with U0126. Association between ERK1 and Nav1.7 following IL-6 treatment was also measured by co-immunoprecipitation. RESULTS: Here we report that in awake animals, direct application of IL-6 to the dura produced dose-dependent facial and hindpaw allodynia. The MEK inhibitor U0126 blocked IL-6-induced allodynia indicating that IL-6 produced this behavioral effect through the MAP kinase pathway. In trigeminal neurons retrogradely labeled from the dura, IL-6 application decreased the current threshold for action potential firing. In response to a ramp current stimulus, cells treated with IL-6 showed an increase in the numbers of action potentials and a decrease in latency to the first spike, an effect consistent with phosphorylation of the sodium channel Nav1.7. Pretreatment with U0126 reversed hyperexcitability following IL-6 treatment. Moreover, co-immunoprecipitation experiments demonstrated an increased association between ERK1 and Nav1.7 following IL-6 treatment. CONCLUSIONS: Our results indicate that IL-6 enhances the excitability of dural afferents likely via ERK-mediated modulation of Nav1.7 and these responses contribute to migraine-related pain behavior in vivo. These data provide a cellular mechanism by which IL-6 in the meninges causes sensitization of dural afferents therefore contributing to the pathogenesis of migraine headache.